Pengaruh Work Life Balance, Burnout, Dan Kepuasan Kerja Terhadap Kinerja Apoteker Rumah Sakit - Purwaningsih, Dini Ayu; Hapsari, Indri; Galistiani , Githa Fungie (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
Hospital pharmacists play a vital role in ensuring safe and effective healthcare services. Their performance can be influenced by various psychosocial factors, including work-life balance, burnout, and job satisfaction. This narrative review aims to examine the relationship between work-life balance, burnout, and job satisfaction in relation to the performance of hospital pharmacists. Relevant literature was retrieved through academic database searches and analyzed descriptively. Findings indicate that poor work-life balance and high burnout contribute to lower job satisfaction, which in turn negatively affects performance. Conversely, good work-life balance and high job satisfaction are positively correlated with improved performance. This review highlights the importance of organizational support in managing the work environment of pharmacists to maintain productivity and pharmaceutical service quality.